Socio-Ecological Dimensions of Spontaneous Plants on Green Roofs - Schrieke, Dean; Lönnqvist, Joel; Blecken, Godecke-Tobias; Williams, Nicholas S. G.; Farrell, Claire (Frontiers in Sustainable Cities, 2021)
Green roofs have the potential to provide socio-ecological services in urban settings that lack vegetation and open space. However, implementation of green roofs is limited by high construction and maintenance costs. Consequently, green roof projects often disproportionately benefit wealthy communities and can further marginalise disadvantaged communities by increasing property values and housing costs. Vegetation cover on green roofs is crucial to their provisioning of socio-ecological services. Evidence suggests that green roof plantings change over time, especially with limited maintenance, and are replaced with spontaneous “weedy” species. This is often perceived as a failure of the original green roof design intent and spontaneous species are usually removed. However, where good coverage is achieved, spontaneous vegetation could provide beneficial services such as stormwater mitigation, habitat provision, and climate regulation. While social norms about “weediness” may limit the desirability of some spontaneous species, research suggests that their acceptability on green roofs increases with coverage. As spontaneous species can establish on green roofs without irrigation and fertiliser, reduced input costs could help facilitate adoption particularly in markets without an established green roof industry. Construction costs may also be reduced in hot and dry climates where deeper substrates are necessary to ensure plant survival, as many spontaneous species are able to colonise shallow substrates and can regenerate from seed. If implemented based on socio-ecological need, green roofs with spontaneous vegetation coverage may apply less pressure to property values and housing costs than conventionally planted green roofs, increasing the resilience of urban communities while limiting gentrification.